Executive functions and depressive symptoms interplay in binge eating disorder: A structural equation model analysis. (13th July 2021) - Rania, Marianna; Aloi, Matteo; de Filippis, Renato; Carbone, Elvira Anna; Caroleo, Mariarita; De Fazio, Pasquale; Segura‐Garcia, Cristina
Abstract: Objective: Executive functions (EF) have been so far investigated as potential endophenotypes for binge eating disorder (BED). However, major critical limitations in previous research, such as the influence of obesity and comorbid depression, prevented any consensus to be reached. The present study investigated the association between depressive symptoms, a broad range of EF and binge eating severity in individuals with obesity and with/without BED, and whether this association may be explained by a mediation or independency model. Method: One hundred and seven participants completed clinical and psychometric examination. Associations between EF, depressive symptoms and binge eating severity were assessed through bivariate correlation analysis, and the magnitude, as well as the direction of associations between variables, was estimated with structural equation model. Results: Two reliable models were tested; results showed that depressive symptoms exhibited significant direct and indirect effects on the severity of binge eating; conversely, EF did not show either significant direct or indirect effect on binge eating severity. Conclusion: Depression contributes more than EF to psychopathology of BED. Thus, clinicians should routinely assess and, eventually, tailor depressive symptoms in treatment to improve the outcomes of patients with BED. Highlights: Depressive symptoms and executive disabilities interplay affects binge eating severity. Within the model, depression severity accounts for binge eating severity to a larger extent than executive disabilities. An integrated approach targeting either depressive symptoms or executive function disabilities may improve outcomes in individuals with binge eating disorder, above all in those suffering from more severe eating and general psychopathology.